Adsorpsi Ion Tembaga (Cu) Dan Ion Besi (Fe) Dengan Menggunakan Arang Hayati (Biocharcoal) Kulit Pisang Raja (Musa sapientum) - Nirmala Nirmala; Vanny M. A. Tiwow; Suherman Suherman (Universitas Tadulako, 2015)
This study determine the contact time, pH, and the optimum concentration of the solution of copper (Cu) and iron (Fe) from skin the plantain (musa sapientum). Advances in the industry today resulted in many human activities that caused increasing impact of the pollution on surrounding of the environment. Environmental pollution by heavy metals being a serious problem along with increasing the use of heavy metals in the industry. The method used in this study was a laboratory experiment using colorimeter. The results showed that the adsorption of copper and iron on the plantain bark influence a time variation of Cu and Fe occurred in the 60 minute and 30 minute (99.64% and 99.54%); variation of pH for Cu and Fe occurrs in pH 4 and pH 3 (99.62% and 99.58%) and variation of concentration for Cu and Fe occurred at 20 ppm and 1 ppm (80.74% and 96.81%), respectively.